HKI sebagai Aset Pembiayaan: Kajian Hukum, Mekanisme, dan Tantangan Implementasinya di Indonesia: Penelitian - Urbanisasi; Anthony Sutedja (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Intellectual Property (IP) is currently recognized as one of the valuable assets that can be owned by individuals and business entities. According to the classification of assets regulated in the Indonesian Civil Code (KUHPerdata), Book II, Chapter I, Article 499, it is stated that “under the law, an object is defined as any good and any right that can be owned.” Intellectual Property falls into the category of intangible assets, as it represents non-physical rights that carry economic value and ownership potential. However, for IP to be legally recognized as the property of an individual or a business entity, it must be formally registered with the Directorate General of Intellectual Property (DJKI). Once the registration process is completed, the owner will be granted an official certificate of ownership, providing legal protection and recognition of their intellectual rights. Alongside the rapid growth of business and the creative economy, Intellectual Property no longer serves merely as a form of protection for intellectual works but has evolved into a high-value economic asset that can be leveraged in various financial activities. One innovative approach to utilizing IP is its use as collateral for bank loans. This concept offers a new alternative for entrepreneurs, particularly those in the creative industries, who often face difficulties in accessing credit due to the lack of conventional collateral such as land or buildings. With legal recognition of IP’s economic value, financial institutions can assess and accept these rights as loan guarantees, thereby expanding access to financing for innovators and creative entrepreneurs.The implementation of IP as banking collateral aligns with the government’s efforts to strengthen the creative economy and foster innovation-driven growth in Indonesia. Nevertheless, several challenges remain, including the valuation mechanism of IP assets, legal protection of pledged rights, and the readiness of financial institutions to assess the associated risks and validity. Therefore, effective collaboration among the government, financial institutions, and IP owners is essential to establish transparent regulations and valuation systems. Such cooperation will enable the use of IP as loan collateral to function efficiently and sustainably, contributing to national economic development.